Grid Based Temperature and Relative Humidity Distribution Map of the Kathmandu Valley - Maharjan, Sangita; Regmi, Ram P. (Journal of Institute of Science and Technology, 2015)
Kathmandu valley has seen visible transformations in its intrinsic climate in recent decades. The atmosphere of the Kathmandu valley has become increasingly uncomfortable, unhealthy and more susceptible to, so far, unanticipated viral and other diseases. The lack of spatial distribution and temporal variation of potential climatic parameters as well as future scenarios have given rise to serious uncertainties with respect to climate change and development of adaptation strategies for sustainable climate of the valley and beyond. An accurate assessment and gridded documentation of prevailing climate at desired resolution is instrumental. Present study has been carried out to develop a high-resolution gridded map of near surface temperature and humidity for Kathmandu valley and its immediate surrounding areas as a starting point to address the foreseen problem of climate change and adaptation. Grid based seasonal and annual distribution map of near surface temperature and humidity have been developed as predicted by numerical simulation at horizontal resolution of 1km2 with the application of WRF Modeling System initializing with NCEP meteorological and USGS land use and terrain elevation data. Model predictions agree well with the available observation data. Journal of Institute of Science and Technology, 2014, 19(1): 7-13